Energy efficiency: a key challenge of the Energiewende. - Kemfert, Claudia; Lorenz, Casimir; Traber, Thure; Opitz, Petra (Springer Nature, 2018)
A significant improvement in energy efficiency is crucial for the success of the energiewende. Energy efficiency plays an important role in reducing primary energy demand and fuel costs, and in many cases, it constitutes the least-cost option for GHG emissions reduction. Other benefits arise from its positive impact on local air quality, human health, and productivity. Energy efficiency investments may trigger positive employment effects through growth in the the building sector, and in the longer term, household energy savings will boost spending in other sectors. This chapter summarizes the German approach to energy efficiency, both in general and at the sectoral level in areas such as building, industry, and transport. It also discusses obstacles that could prevent an increase in energy efficiency from a general viewpoint and in the specific case of Germany. Section 7.2 provides a survey of the energy efficiency targets identified in Germany s Energy Concept 2050 and other documents, and discuss the results of this policy, which have been mixed to date. Section 7.3 then provides a sectoral analysis, looking specifically at the building, industry, and transport sectors. Section 7.4 looks at specific energy efficiency policies going forward, in particular the National Action Plan on Energy Efficiency (NAPE) and some key future challenges. Section 7.5 concludes.
Keywords: Energie; Energiewende; Energieeffizienz; Wirtschaftssektor; Planungsziel; Gebäude; Industrie; Verkehr